The black stallion - Farley, Walter, 1915- (New York : Random House, 2002)
The story of the understanding and love between a boy and a magnificent wild horse and the adventures and dangers they shared.
"A Yearling book."
Wilson's Children
Child Study Children's Book Committee
Library Journal
6.5
5-8
Keywords: Horses -- Fiction; Horses -- Fiction